NEURO-MIŠIĆNE KARAKTERISTIKE MAKSIMALNE SPRINTERSKE BRZINE - Milan Čoh; Goran Bošnjak (University of Banja Luka, Faculty of physical education and sport, 2010)
Locomotor speed sprint-type is one of the most important skills, which generates the success ofathletes in many sports situations. The maximum speed that a person can manifest in any kind ofmovement depends on a number of different factors. These factors are related to morphologicaland physiological characteristics, the mechanisms of power, sex, age, motility skills, interintramuscularcoordination and optimal biomechanics of movement techniques. The developmentof maximum sprint speed has certain laws that relate to the level of motility abilities, morphologicalcharacteristics, the degree of biomechanical efficiency and rationality of movement, and requiresvery subtle inter-muscular coordination of muscle groups of the lower extremities. The primary aimof speed training is to create an optimal model of movement, which is based on the conformity ofaction of muscle groups. Precise control of movement is controlled by the cerebellum and theinformation that they arrive there, mostly through proprioreceptors which are located in thecapsule and connective elements of the muscle. Since the optimum neuro-muscular coordinationof the main is limiting factor for maximum speed, and that could explain the dynamics and changesin frequency and length of steps in the realization of maximum speed, it is necessary to explain thefunction of the central nervous system that generate muscle force. The development of maximumsprint speed is long-term process, which is related to the optimal control agonistic and antagonisticmuscle groups in the structure of the sprint steps. The establishment of proper dynamic stereotypeis a long process, which must have clearly defined methods and must start at an early age of youngathletes.